Bonding and bending in zirconium(IV) and hafnium(IV) hydrazides - Herrmann, Heike; Lloret Fillol, Julio; Gehrmann, Thorsten; Enders, Markus; Wadepohl, Hubert; Gade, Lutz H. (Chemistry - a European journal, 2008)
Reaction of the dichloro complexes [M(N2TBSNpy)Cl2] (M=Zr: 1, Hf: 2; TBS: tBuMe2Si; py: pyridine) with one molar equivalent of LiNHNPh2 gave mixtures of the two diastereomeric chlorohydrazido(1−) complexes [M(N2TBSNpy)(NHNPh2)Cl] (M=Zr: 3 a,b, Hf: 4 a,b) in which the diphenylhydrazido(1−) ligand adopts a bent κ1 coordination. This mixture of isomers could be cleanly converted into the deep green diphenylhydrazido(2−) complexes [Zr(N2TBSNpy)(NNPh2)(py)] (5) and [Hf(N2TBSNpy)(NNPh2)(py)] (6), respectively, by dehydrohalogenation with lithium hexamethyldisilazide (LiHMDS) in the presence of one molar equivalent of pyridine. Both complexes contain a linearly coordinated hydrazinediide for which a DFT-based frontier orbital analysis established bonding through one σ and two π orbitals. A high polarity of the MN bond was found, in accordance with the description of hydrazinediide(2−) acting as a six-electron donor ligand. The pyridine ligand in [M(N2TBSNpy)(NNPh2)(py)] (M=Zr: 5, Hf: 6) is substitutionally labile as established by line-shape analysis of the dynamic spectra (ΔG≠=19 kcal mol−1). A change in denticity of the hydrazido unit from κ1 to κ2 was studied by DFT methods. Both forms are calculated to be very close in energy and are only separated by shallow activation barriers, which supports the notion of a rapid κ1 to κ2 interconversion. This process is believed to happen early on in the NN scission in the presence of coupling reagents. Frontier orbital and natural population analyses suggest that a primarily charge-controlled nucleophilic attack at Nα is unlikely whereas interaction with an electrophile could play an important role. This hypothesis was tested by the reaction of 5 and 6 with one molar equivalent of B(C6F5)3 to give [Zr(N2TBSNpy)(NNPh2)B(C6F5)3] (7) and [Hf(N2TBSNpy)(NNPh2)B(C6F5)3] (8). In these products, B(C6F5)3 becomes attached to the Nα atom of the side-on bound hydrazinediide and there is an additional interaction of an ortho-F atom of a C6F5 ring with the metal centre.
Published online: August 4, 2008
Gesehen am 23.11.2022